Blood collection on filter paper for HIV antibodies detection: experience of SampaCentro Project - Marcia J. Castejon; Rosemeire Yamashiro; Carmem A. F. Oliveira; Carmen Lúcia Soares; Maria Amélia S. M. Veras (Sociedade Brasileira de Patologia Clínica, 2015)
Introduction: Blood samples collected on filter paper (dried blood spot [DBS]) is an immunoassay that has been used for antibodies screening. Objective: To evaluate the strategy of DBS blood collection for detection of HIV antibodies, evaluation of Q-Preven HIV 1 + 2 - DBS kit lot, and to analyze the stability of DBS samples. Methods: Blood collection on DBS was performed according to World Health Organization (WHO) recommendations. The evaluation of the kit lot for HIV antibodies detection was performed using delta (d) values from the results of 774 DBS samples from volunteers men who have sex with men (MSM) recruited in the central region of São Paulo city, Brazil. Results: DBS blood collection was performed without complications. The positive (5.26) and negative (5.23) delta values allowed to clearly differentiate HIV antibodies reactive and non-reactive samples. We observed good performance of the kit lot and samples were stable on DBS form. Conclusion: Blood collection on DBS is feasible for the study of MSM population and is suitable for laboratory routine. The overall performance of Q Preven HIV-1 + 2 - DBS kit was satisfactory, having reached the quality levels required for the development of this study.